Performance Measures for Developing the Performance Measurement System: Systematic Literature Review Approach - Nor Mahirah, Mustapha; Sorooshian, Shahryar; Noor Azlinna, Azizan (Romanian Society for Quality Assurance - SRAC, 2017)
Determining the most relevant performance measures is the major challenges that organizations have to encounter for generating an effective performance measurement system (PMS). Selecting performance measures can be characterized as a multiple criteria decision making (MCDM) problems, as it involves a number of measures and mutual interdependencies. The objective of this paper is to bring up the list of performance measures that might be functional in developing the PMS. Based on the four main steps of systematic review of performance management and measurement literature concerning the model to evaluate the performance, the paper picks out an arrangement of performance measures that might be can be used in PMS development. The feasibility of the finding is authenticated because the literatures chosen in this study were theoretically established.The list of performance measures, that can be used as a managerial tool to control performance in any type of organization are provided. Using the set of performance measures identified in this study, it facilitates the work of policy and decision makers as it acts as a reference and foundation on which to evaluate in their organizational performance and improves the quality of the future PMS.This paper presents a narrative listing for driving managers or researchers towards the choice of performance measures using precise approach, and contribute in the collection of the literature in the field of performance measurement and management.